2012
DOI: 10.1080/ac.67.2.2154207
|View full text |Cite
|
Sign up to set email alerts
|

Clinical fi ndings associated with cardiovascular autonomic dysfunction in adult sickle cell anaemia patients

Abstract: Significant cardiac morbidity is associated with abnormal cardiovascular autonomic function in sickle cell anaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…Although the effect size for STAI Y1 was small in the multivariate analysis, it was significant, suggesting that treatments directed at relieving anxiety may help reduce vascular reactivity. Baseline HRV was lower in SCD, as reported by others, [39][40][41][42][43] but there were no differences between controls and patients with SCD in the direct measures of cardiac autonomic activity in response to thermal stimuli. Cardiac autonomic activity and peripheral vascular autonomic reactivity are related to each other via complex neural mechanisms, but are not equivalent.…”
Section: Discussionsupporting
confidence: 79%
“…Although the effect size for STAI Y1 was small in the multivariate analysis, it was significant, suggesting that treatments directed at relieving anxiety may help reduce vascular reactivity. Baseline HRV was lower in SCD, as reported by others, [39][40][41][42][43] but there were no differences between controls and patients with SCD in the direct measures of cardiac autonomic activity in response to thermal stimuli. Cardiac autonomic activity and peripheral vascular autonomic reactivity are related to each other via complex neural mechanisms, but are not equivalent.…”
Section: Discussionsupporting
confidence: 79%
“…The role of hypoxemia/hypoxia on ANS dysfunction has been reinforced by studies in rats showing that chronic hypoxia causes cell loss in the nucleus ambiguous, a structure from which several vagal efferent axons innervate ganglionated plexuses in the dorsal surface of cardiac atria, which in turn may have different functional roles in cardiac regulation [34]. SCA patients with the most severe form of the disease [10], at risks for developing frequent vaso-occlusive crises [11] or acute chest syndrome [12], or with leg ulcers and erectile dysfunction [35], have a depressed ANS activity and a reduced parasympathetic activity. These findings suggest a role of parasympathetic withdrawal and sympathetic predominance in the pathophysiology of several sickle cell complications.…”
Section: Discussionmentioning
confidence: 99%
“…In one of the earliest studies evaluating HRV in SCD, Romero et al found that 58% of SCD subjects had abnormal cardiac autonomic balance, implying a role for dysautonomia in the high frequency of sudden death in SCD patients [44]. More recently, autonomic activity has been associated with disease severity in SCD [45,46,47]. Reduced parasympathetic activity at baseline has been associated with increased risk of VOC [46] and acute chest syndrome [48].…”
Section: Autonomic Dysfunction and Peripheral Vasoreactivity In Scdmentioning
confidence: 99%